2017
DOI: 10.3389/fmicb.2017.00907
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Metagenomic Analysis of Tetracycline Resistance in Cheese Bacteria

Abstract: Metagenomic techniques have been successfully used to monitor antibiotic resistance genes in environmental, animal and human ecosystems. However, despite the claim that the food chain plays a key role in the spread of antibiotic resistance, metagenomic analysis has scarcely been used to investigate food systems. The present work reports a functional metagenomic analysis of the prevalence and evolution of tetracycline resistance determinants in a raw-milk, blue-veined cheese during manufacturing and ripening. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
1
17
2
Order By: Relevance
“…enterica and E. coli. In addition, these authors showed that various tetracycline resistance determinants were embedded or in proximity to sequences homologous to those of LAB-derived species (9). It is reasonable to believe that members of LAB isolated from dairy products can act as reservoirs for different AR genes, as was previously reported (9,12,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…enterica and E. coli. In addition, these authors showed that various tetracycline resistance determinants were embedded or in proximity to sequences homologous to those of LAB-derived species (9). It is reasonable to believe that members of LAB isolated from dairy products can act as reservoirs for different AR genes, as was previously reported (9,12,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, these authors showed that various tetracycline resistance determinants were embedded or in proximity to sequences homologous to those of LAB-derived species (9). It is reasonable to believe that members of LAB isolated from dairy products can act as reservoirs for different AR genes, as was previously reported (9,12,(28)(29)(30). In our study, the use of a combined approach involving both function-based and in silico sequencing-based analyses to characterize a large metagenomics library built with DNA isolated from different compartments of the cheese production chain allowed us to identify L. lactis as a major reservoir and source of AR determinants within the dairy production chain.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance of AMR is currently based on the isolation of indicator microorganisms and their phenotypic characterisation, but this culture‐dependent approach does not provide complete information on the mechanisms driving AMR or on the presence or spread of AMR genes throughout the food chain. Metagenomics is a powerful tool that allows culture‐independent analysis of complex microbial communities and thus has potential applications in AMR surveillance (Bonham et al., ; Flórez et al., ; Walsh et al., ). It can provide access to all the genetic resources in a given environmental niche, which is essential for obtaining the genomes of fastidious or non‐culturable microorganisms.…”
Section: Introductionmentioning
confidence: 91%
“…The ability of bacteria to resist the action of one or several antimicrobial agents through bacterial gene mutations or by acquiring exogenous resistance genes carried on mobile elements is defined as antimicrobial resistance (AMR) (ECDC, 2017). Acquired resistance to some antimicrobials is already so widespread as to compromise their value for the treatment of life-threatening infections (EFSA BIOHAZ Panel, 2008). Harmonised outcome indicators have been jointly established by the European Centre for Disease Prevention and Control (ECDC), the European Food Safety Authority (EFSA) and the European Medicines Agency (EMA) to assist Member States in assessing the progress made in reducing antimicrobial use and AMR both in humans and food-producing animals (ECDC, EFSA BIOHAZ Panel and CVMP, 2017).…”
mentioning
confidence: 99%
“…Antimicrobials are used globally both for humans and animals to obviate and treat contagious diseases (O'neill, 2014). Furthermore, in some countries, antimicrobials are used in animal breeding as growth promoters (Flórez et al, 2017). Antimicrobial agents are one of the medicinal innovations of humanity that allows us to cure both human and veterinary infections of microbes.…”
Section: Introductionmentioning
confidence: 99%